Measurement of target radial velocity - D. I. Popov (Известия высших учебных заведений России: Радиоэлектроника)
The multichannel and single-channel measuring instruments of target radial velocity with use multifrequency signals at presence correlated and non-correlated handicapes are synthesized. The analysis of the synthesized measuring instruments of target radial velocity is carried out.